A decolonial reading of the CNN framing of the Ebola crisis. - Paradzai, Jealous (Midlands State University, 2017)
This is a critical discourse analysis of how ideological domination and power were reproduced in the CNN representations of Africa and Africans in the coverage of the Ebola crisis. The research also sought to establish if the CNN could have provided a conduit for racism in its framing of the disease. The research used a qualitative research methodology. The research was theoretically informed by the theories of representation and decolonial theory. It generally emerged in this thesis that Africa and Africans were represented negatively as place of disease and as a place of danger. The African comes in largely in the form of a problem and they are represented as a white man‟s burden in the sense that there is nowhere in the CNN coverage are Africans shown as having the agency to stop the outbreak of the disease. There is no internal initiative by African systems to help stop the spread of Ebola, all help is marshaled from United States of America and United Kingdom. CNN could also have provided a conduit for racism in its coverage in the sense that the death of Americans is held apart from that of Africans. Europeans who are infected with Ebola are generally valorized and held in high esteem but the Africans are blamed for the spread of Ebola. Heroism is built around doctors and nurses from the United States of America and the west in general. This resonates with existing literature on the representations of diseases such as AIDS which was largely attributed to African cultural habits, norms and values. Racism is also inferred in the coverage of Ebola by CNN through its persistent blame on African culture and behavior. The white saviour complex is perpetuated in the coverage of the Ebola crisis as Africans are represented as helpless and have to rely on the goodwill of kind hearted whites to save them from Ebola which is basically attributed by the CNN as Africa‟s Ebola.